(untitled) (Applied Biological Research, 2012)
This study was aimed to determine the effect of varying levels of nitrogen fertigation on growth of Kail pine (Pinus wallichiana) seedlings in nursery conditions. The germinated seedlings were fertilized at weekly interval with Ingestad pretreatment nutrient solution of N (1.98 mg week-1) and P, K, Ca and Mg (in 100: 13: 65: 7: 8.5 ratio) @ 25 ml seedling-1 for one month as pretreatment. The pre-treated seedlings were divided into 12 lots and fertilized with either of the nitrogen doze @ 0 (with or without fertigation), 0.99, 1.98, 2.97, 3.96, 4.95, 5.94, 6.93, 7.92, 8.91 and 9.90 mg dissolved in 50 ml water alongwith fixed levels of P, K, Ca and Mg seedling-1 week-1 upto 28 weeks. Nitrogen significantly increased seedling height, biomass, relative growth rate and other quality parameters. Quality seedlings of Kail pine were produced at the nitrogen addition @ 7.92 mg seedling-1 week-1 for the first growing season at nursery. It increased seedling height by 113.7%, root collar diameter by 78% and dry biomass by 78.8% as compared to control. However, relative growth rate was highest at 5.95 mg of nitrogen addition rate.